Social Network Investigation of a Syphilis Outbreak in Ottawa, Ontario - H D’Angelo-Scott; J Cutler; D Friedman; A Hendriks; AM Jolly (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: The incidence of syphilis in Ottawa, Ontario, has risen substantially since 2000 to six cases per 100,000 in 2003, again to nine cases per 100,000 in 2007, and recently rose to 11 cases per 100,000 in 2010. The number of cases reported in the first quarter of 2010 was more than double that in the first quarter of 2009.